Environmentally Friendly Technology at PT Inalum: Implementation and Challenges within the Framework of Environmental Law in Indonesia - Batubara, Aznina Lembayung; Hutapea, Ali Alatas; Dittowisono, Aghyfariz (Law Review, 2024)
Environmental-friendly technology plays a crucial role in modern industries, including PT Inalum, a leading aluminum producer in Indonesia. The company has implemented various innovations to minimize environmental impacts, such as utilizing renewable energy sources, waste management systems, and emission reduction technologies. These efforts aim to comply with national environmental regulations, such as Law Number 32 of 2009 on Environmental Protection and Management, and international commitments like the Paris Agreement 2016. This study examines the challenges faced by PT Inalum in implementing sustainable technology. The research employs normative legal analysis and case study methods, focusing on regulatory reviews and corporate sustainability practices. Key challenges include regulatory uncertainty, overlapping government policies, and weak law enforcement mechanisms. Additionally, high investment costs for green technology adoption pose a significant barrier to achieving optimal environmental sustainability. The findings indicate that despite PT Inalum’s commitment to environmentally friendly practices, legal and economic obstacles hinder full regulatory compliance. The study suggests the need for clearer policies, stronger enforcement mechanisms, and financial incentives to encourage sustainable industrial transformation. Enhanced collaboration between government authorities and industry stakeholders is essential to creating a more effective and efficient sustainability framework.